The encyclopedia of beaches and coastal environments. - Schwartz, Maurice L. (Straudsburg, PA Hutchinson Ross Publication, 1982)
Encyclopedia of earth sciences, v.15
Keywords: Coastal ecology--Dictionaries.; Beaches--Dictionaries.; Coasts--Dictionaries.